ASSOCIATION OF DERMATOGLYPHIC PATTERNS WITH OVARIAN CANCER - Yenny Febriany; Triwani Triwani; Herman Yasin; Joko Marwoto (Majalah Kedokteran Sriwijaya, 2022)
Ovarian cancer passed down in the family through inheritance of BRCA1 and BRCA2 genes that have been mutated. The objective of this research was to explore the relationship between dermatoglyphic patterns and ovarian cancer. Research method used an observational analytic using case-control design taking place at Obstetrics Inpatient Ward in RSUP Dr. Mohammad Hoesin Palembang. Samples of case and control groups were selected by using consecutive sampling method (Non probability). This method included all patients that meet the inclusion criteria as part of the sample in order to fullfill number of samples required to perform the analysis, and sample selection was done during certain period. Chi-Square test was used to analyze correlation between fingerprint patterns (Arch, Loop, and Whorl) and ovarian cancer. Independent sample t-test used to find average discrepancy of TRC (Total Ridge Count) and ATD angle. These statistical analyses were done by using SPSS for Windows. Research result indicated that most ovarian cancer samples had dermatoglyphic pattern; followed by Loop (52.4%) Whorl (44.2%), and Arch (3.3%). Dankmeijer and Furuhata indices of ovarian cancer were 3.91 and 68.45, respectively. There was a significant relationship between ovarian cancer patients’ and non-ovarian cancer patients’ fingerprints pattern, with Whorl pattern p value = 0.004 and Loop pattern p value = 0.005. There was no significant difference of Total Ridge Count (TRC) between ovarian cancer patients and non-ovarian cancer patients, with p value = 0.238. There was no significant difference of average angle of right ATD, with p value = 0.893, and average angle of left ATD, with p value = 0.323, between ovarian cancer patients and non-ovarian cancer patients.